Pengaruh Profitabilitas dan Dewan Pengawas Syariah terhadap Islamic Social Reporting dengan Moderasi Ukuran Perusahaan - Roziana Nur Aini; Iwan Fakhruddin; Azmi Fitriati; Ira Hapsari (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to examine and analyze the effect of profitability, the number of Sharia Supervisory Board (SSB) members, and the frequency of SSB meetings on Islamic Social Reporting (ISR), with company size as a moderating variable in Sharia Commercial Banks in Indonesia. The research uses secondary data obtained from the annual reports of Sharia Commercial Banks during the period 2016–2022, with a total sample of 94 using a pooled unbalanced panel method or census method. Data analysis was conducted using panel data regression with the assistance of STATA version 17, and included the Chow test, Hausman test, Breusch-Pagan Multiplier test, diagnostic tests, and hypothesis testing. The results show that profitability has no significant effect on ISR disclosure. The number of Sharia Supervisory Board members has a negative effect on ISR, while the frequency of SSB meetings has a positive effect. Company size does not moderate the effect of profitability on ISR, but it does moderate the effect of the number of SSB members on ISR. These findings highlight the importance of optimizing the role of the Sharia Supervisory Board and strengthening corporate organizational structure to enhance the quality of Islamic social reporting.